Application of cross polarisation techniques to dynamic nuclear polarisation dissolution experiments - Pérez Linde, Angel Joaquin (2010)
Dynamic Nuclear Polarisation (DNP) was suggested for the first time by Albert Overhauser in early 1950s. In DNP experiments the polarisation from electrons can be transferred to nuclei by irradiation of the electron resonance line. There are several possible mechanisms for polarisation transfer that involve DNP in solid state depending on the width of the electron line in respect to the nuclear Larmor frequency. In this thesis, the efficiency of TEMPO radical (2,2,6,6 tetramethilpiperidine, 1 oxyl) for DNP is demonstrated in combination with nuclear polarisation transfer techniques for dissolution experiments. New cryo-probes were developed for DNP and cross polarisation (CP) for operation temperatures as low as 1.5 K. Two of them were designed for dissolution experiments. Some published sequences of nuclear polarisation transfer were tested at low temperatures and compared. Novel sequences were implemented for efficient CP in organic samples doped with TEMPO to allow for a consecutive dissolution experiment. The combination of DNP with new CP sequences at low temperatures, achieved at least twice the 13C polarisation obtained with DNP and in a substantially shorter time (between 5 to 10 minutes) in samples doped with TEMPO. The polarisation levels obtained in samples of [13C-1] labelled Na acetate in a few minutes was comparable to the polarisation obtained with trityl radicals in a few hours. In addition, another strategy was investigated by using brute force polarisation as a mechanism for achieving large levels of nuclear spin order. The problem presented by this method is the long relaxation time required to obtain the thermal equilibrium polarisation. By doping with lanthanides samples of [13C-1] labelled Na acetate in 1:1 glycerol-water, it was possible to obtain thermal equilibrium for a 13C spin system in less than one hour.